Acupuncture-Analgesia-Mediated Alleviation of Central Sensitization. (7th March 2019) - Lai, Hsiang-Chun; Lin, Yi-Wen; Hsieh, Ching-Liang
Abstract : Pain can trigger central amplification called central sensitization, which ultimately results in hyperalgesia and/or allodynia. Many reports have showed acupuncture has an analgesic effect. We searched the related article on PubMed database and Cochrane database to discover central sensitization pathway in acupuncture analgesia. We summarized that acupuncture enhances the descending inhibitory effect and modulates the feeling of pain, thus modifying central sensitization. The possible mechanisms underlying the analgesic effects of acupuncture include segmental inhibition and the activation of the endogenous opioid, adrenergic, 5-hydroxytryptamine, and N-methyl-D-aspartic acid, α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid/kainate pathways. Moreover, acupuncture can locally reduce the levels of inflammatory mediators. In clinical settings, acupuncture can be used to treat headache, neuropathic pain, low back pain, osteoarthritis, and irritable bowel syndrome. These mechanisms of acupuncture analgesia may be involved in the alleviation of central sensitization.